Ethics as language in The Book of the Knight of the Tower - Ruszkiewicz, Dominika (Studia Anglica Posnaniensia, 2025)
In The Book of the Knight of the Tower, the father-narrator teaches his daughters how to recognize cleverly disguised deceivers who speak both truly and falsely. In the course of the Knight’s conduct manual for girls, it becomes clear that the words are divided into good and evil, depending on the speaker’s intention, while the responsibility for discerning a true word from a false one lies with the respondent, most frequently a young lady. In my paper I will examine the writer’s engagement with female speech against a socio-historical context, on the one hand, and against St. Thomas Aquinas’s typology of sins presented in Summa Theologica, on the other. My aim is to show that the moral lessons imparted from parent to child, especially lessons on the use of speech, should be understood in terms of practical ethics in that they move beyond a concern for the individual’s moral conscience and have wider implications for the family’s good name within the community and indeed for society in general.